Death inducer-obliterator 1 (Dido1) is a BMP target gene and promotes BMP-induced melanoma progression - Braig, S.; Bosserhoff, Anja Katrin (Oncogene, 2013)
Bone morphogenetic proteins (BMPs) are known to play an important role in melanoma development and progression. However, the downstream targets of BMPs have not been investigated thus far. Therefore, we treated melanoma cell lines with the Smad-specific BMP inhibitor Dorsomorphin and performed a cDNA microarray. We identified death inducer-obliterator 1 (Dido1) as a BMP-specific Smad-regulated target gene, which was confirmed by qRT-PCR, immunofluorescence staining and electrophoretic mobility shift assay experiments. An analysis of Dido1 expression revealed an upregulation of Dido1 levels in melanoma cell lines and tissues compared with normal melanocytes. Colony-formation assays showed that siDido1-transfected cells formed significantly smaller colonies when grown in soft agar compared with control cells. In addition, fluorescence-activated cell sorting and western blot experiments revealed that transfection of melanoma cells with Dido1 small interfering RNAs led to an upregulation of apoptosis. Furthermore, cell migratory and invasive potentials were strongly reduced in siDido1-transfected cells compared with control cells. Finally, we demonstrated that Dido1 induces the expression of Integrin αV, thereby promoting the attachment, migration, invasion and apoptosis resistance of melanoma cells. © 2013 Macmillan Publishers Limited All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: bone morphogenic protein; Dido1; integrin αV; invasion; malignant melanoma; migration